ChemInform Abstract: Self‐Catalyzed Mannich‐Type Reaction of Enolizable Cyclic 1, 3‐Dicarbonyls to Acyclic Nitrones: An Entry to Functionalized β‐Enamino Diones. Issue 34 (1st August 2013) - Cordaro, Massimiliano; Risitano, Francesco; Scala, Angela; Rescifina, Antonio; Chiacchio, Ugo; Grassi, Giovanni
Abstract The advantages of the new title synthesis are the mild conditions, simple work‐up, and the straightforward access to important synthetic intermediates.